Unveiling the role of Programmed Cell Death Ligand-1 (PDL-1) expression in cervical squamous cell carcinoma: Clinical insights and pathological implications - Sulistiawati, Yuniarni; Arifuddin, Sharvianty; Syahrir, Syahruni; Masadah, Rina; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2026)
Background: Squamous Cell Carcinoma Cervix (SCC) is a major contributor to cancer-related mortality, closely linked to chronic HPV infection. Programmed Cell Death Ligand-1 (PD-L1) has surfaced as a prospective biomarker in several cancers, including cervical squamous cell carcinoma (SCC); however, its clinical and pathological relevance in untreated patients has not yet been thoroughly investigated.Methods: This cross-sectional study included 66 untreated patients diagnosed with cervical SCC, with clinicopathological data and formalin-fixed paraffin-embedded tissue samples collected from Universitas Hasanuddin Teaching Hospital. PD-L1 expression was evaluated using the Tumor Proportion Score (TPS) and categorized as negative (